The impact of urban form on the relationship between vehicle miles traveled and air pollution - Nicole S. Ngo; Zhenpeng Zou; Yizhao Yang; Edward Wei (Transportation Research Interdisciplinary Perspectives)
In the past century, there have been major shifts in the built and natural environment across the U.S. as urban areas grow to accommodate larger urban populations. Yet, there is little research on how these changes in urban form could affect an important relationship in transportation and health: vehicle miles traveled (VMT) and air pollution. For example, studies show urban areas typically have a higher building density, which can trap in more air pollution relative to rural or open spaces where pollution can disperse more widely. A lack of detailed data on VMT, as well as methodological challenges have made assessing this relationship difficult. To address this, we use a quasi-experimental framework and a unique dataset to examine how a dramatic change in vehicle miles traveled (VMT) during the COVID-19 pandemic affected air pollution and if or how urban form moderated this relationship. We use detailed county-level daily VMT and air quality data in the contiguous U.S. between January and August 2020. Our results show statistically significant positive correlations between VMT and air pollution in urban counties, but in rural counties the marginal effect of VMT on air pollution was either statistically insignificant or very small. Results from this study suggest that efforts to reduce the marginal impact of VMT or vehicle emissions in urban areas could lead to a greater improvement in air quality when compared to more rural counties due to the built environment.